2019
DOI: 10.22454/fammed.2019.424025
|View full text |Cite
|
Sign up to set email alerts
|

Family Physician Burnout and Resilience: A Cross-Sectional Analysis

Abstract: Background and Objectives: Current physician burnout levels are at historically high levels, especially in family medicine, with many factors playing a role. The goal of this study was to understand demographic, psychological, environmental, behavioral, and workplace characteristics that impact physician wellness and burnout, focusing on family medicine physicians and residents. Methods: Survey respondents were 295 family medicine residents and faculty members across 11 residency programs within the Residency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 18 publications
(27 reference statements)
3
31
1
1
Order By: Relevance
“…10 Physician burnout and the resultant decreased productivity may exacerbate the previously predicted shortfall of 45,000 to 90,000 physicians in the United States by 2025. 11 Occupational stress has resulted in concern about burnout rates among emergency room physicians, 12 anesthesiologists, 13 radiologists, 14 general internists, 15 family physicians, 16 oncologists, 17 psychiatrists, 18 general surgeons, 19 trauma surgeons, 20 physiatrists, 21 cardiologists, 4 dermatologists, 22 obstetrician-gynecologists, 23 gastroenterologists, 24 residents, and even medical students. 25 In addition to worsened patient outcomes and satisfaction, physician health may be at risk.…”
Section: Scope and Impact Of Physician Burnoutmentioning
confidence: 99%
“…10 Physician burnout and the resultant decreased productivity may exacerbate the previously predicted shortfall of 45,000 to 90,000 physicians in the United States by 2025. 11 Occupational stress has resulted in concern about burnout rates among emergency room physicians, 12 anesthesiologists, 13 radiologists, 14 general internists, 15 family physicians, 16 oncologists, 17 psychiatrists, 18 general surgeons, 19 trauma surgeons, 20 physiatrists, 21 cardiologists, 4 dermatologists, 22 obstetrician-gynecologists, 23 gastroenterologists, 24 residents, and even medical students. 25 In addition to worsened patient outcomes and satisfaction, physician health may be at risk.…”
Section: Scope and Impact Of Physician Burnoutmentioning
confidence: 99%
“…Hardiness refers to one's resilience and ability to cope with stressful and unexpected situations. Studies have shown that higher levels of resilience correlates to improved stress tolerance (Bartone, 1999;Kalantar et al, 2013;Sandvik et al, 2013) and may be protective effects against post-traumatic stress disorder (Bartone, 1999;Escolas et al, 2013) and burnout symptoms (Buck et al, 2019). Hardiness is characterized by challenge, the ability to be flexible and grow from failure, control, acknowledging that managing one's life is always possible and commitment, having a sense of meaning and purpose with the ability to stay motivated (Kobasa, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…
hysicians in training experience high levels of burnout with associated higher rates of stress, anxiety, depression, suicidal ideation, and substance abuse. [1][2][3][4] Physician burnout also affects patients by predisposing doctors to make medical errors and provide poorer quality of care. 5,6 Residency training can be a particularly stressful time in a physicians' career, with prior work showing that residents at highest risk of reporting burnout are female, of non-Hispanic White ethnicity, younger, and graduates of US medical schools.
…”
mentioning
confidence: 99%
“…5,6 Residency training can be a particularly stressful time in a physicians' career, with prior work showing that residents at highest risk of reporting burnout are female, of non-Hispanic White ethnicity, younger, and graduates of US medical schools. 1,2,[7][8][9][10] Studies have also found that burnout is more prevalent in physicians who are unmarried and who experience higher levels of family stress. 11,12 Recent literature has also linked physician burnout to psychological and interpersonal contributors like resilience, social support, and self-care practice.…”
mentioning
confidence: 99%